2015
DOI: 10.1093/europace/euv344
|View full text |Cite
|
Sign up to set email alerts
|

Near zerO fluoroscopic exPosure during catheter ablAtion of supRavenTricular arrhYthmias: the NO-PARTY multicentre randomized trial

Abstract: AimsAim of this study was to compare a minimally fluoroscopic radiofrequency catheter ablation with conventional fluoroscopy-guided ablation for supraventricular tachycardias (SVTs) in terms of ionizing radiation exposure for patient and operator and to estimate patients' lifetime attributable risks associated with such exposure.Methods and resultsWe performed a prospective, multicentre, randomized controlled trial in six electrophysiology (EP) laboratories in Italy. A total of 262 patients undergoing EP studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
115
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(125 citation statements)
references
References 33 publications
5
115
1
Order By: Relevance
“…Classification of AF recurrences to the LRAF (3–12 months) and the VLRAF (>1 year) was arbitrary, but in concordance with current reports123456789171820252627. An intermittent rhythm monitoring after ablation by only 24-hour Holter-recording may underestimate the AF recurrence rate, especially in asymptomatic cases, and undetected AF recurrence within the first postoperative year may lead to its misinterpretation as VLRAF in some patients1.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Classification of AF recurrences to the LRAF (3–12 months) and the VLRAF (>1 year) was arbitrary, but in concordance with current reports123456789171820252627. An intermittent rhythm monitoring after ablation by only 24-hour Holter-recording may underestimate the AF recurrence rate, especially in asymptomatic cases, and undetected AF recurrence within the first postoperative year may lead to its misinterpretation as VLRAF in some patients1.…”
Section: Discussionsupporting
confidence: 58%
“…Longer procedure times may reflect a more complex anatomy and substrate, but also they can be affected by technology and experience of the operator. Recently, it has been reported that the current trend towards the use of “near zero” approach is adopted in different electrophysiological procedures, in order to protect the patients and staff from the harmful effects of ionizing radiation2021.…”
Section: Discussionmentioning
confidence: 99%
“…Authors of the randomized NO-PARTY trial assessed lifetime attributable risks of cancer incidence and mortality from equivalent organ doses calculated with Monte Carlo code, according to the Biological Effects of Ionizing Radiation empirical risk models [23]. According to their results, the lifetime attributable cancer incidence ranged between 7.3 (95% confidence interval: 3.4–12.8)–11.0 (6.0–18.6) for males and 8.2 (5.0–12.8)–15.4 (9.9–25.3) for females for minimal fluoroscopy approach and 195 (111–315)–321 (198–512) and 241 (165–350)–486 (333–773) for females for the conventional approach, per 100 000 individuals (depending on age).…”
Section: Discussionmentioning
confidence: 99%
“…[312,15] First, it is a nonrandomized study performed by medical staff that are already trained in NXR. [11] The success of the ablation procedure was confirmed acutely and within the observation period.…”
Section: Limitationsmentioning
confidence: 99%